Problems and prospects for the future career: “Public and municipal administration” students’ estimates - V S Muhametzhanova; E A Ivlev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
In recent years, in Russia both official and media discourses have emphasized the need to modernize, optimize and reform the institutions of public and municipal administration as basic means of socio-economic and political development of the country. Unfortunately, quite often different organizational forms within the system of social management encounter not only institutional or objective obstacles, but also subjective problems determined by the “quality” of human resources. For decades, the concept “official” in the Russian public opinion retains its negative connotations; at the same time, the corresponding professions are extremely attractive for the younger generations as a guarantee of not high income, but rather of a stable financial and social status. The authors compare the results of two surveys conducted in 2011 and 2015 on the samples of “public and municipal administration” students in the Peoples’ Friendship University of Russia to reveal if they are committed to the stereotypes of mass consciousness on the problems and prospects of the state and municipal employees as a professional group with specific formal and informal corporate rules and requirements, which tends to remain closed for a common man. The authors recognize the limits for comparing two surveys data due to the modification of the questionnaire; however, they identify a number of important trends in the future state and municipal employees’ perception of ethical requirements, public expectations and claims to their work.